Effects of Product Quality, Service Quality, Price Perception, and Reputation on Purchase Intention: The Mediating and Moderating Roles of Trust in Shopee as an Online Shopping E-Commerce - Atika Ayu Listari; Arif Hartono (Budapest International Research and Critics University, 2022)
The research entitled